2010
DOI: 10.1088/0953-8984/22/11/115701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Co doping on the transport properties and superconductivity in CeFe1 −xCoxAsO

Abstract: A series of CeFe(1-x)Co(x)AsO oxyarsenide compounds with Co doping on iron sites (x = 0-0.2) have been synthesized by a solid state reaction method. The effects of Co doping on the electrical transport properties and superconductivity were analyzed with a special emphasis on the analysis of thermopower. Undoped CeFeAsO shows an electrical resistivity anomaly at about 150 K, which was ascribed to a spin-density-wave (SDW) instability. This anomaly is suppressed and a superconducting transition occurs at T(c) = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…In the Ce(Fe,Co)AsO series, superconductivity appears while the magnetic order at T Fe N is quickly suppressed upon substituting Fe with Co. 14,15 The Ce Néel temperature slightly increases near the Fe-3d magnetic instability, but shows a nearly unchanged value on further increasing the Co concentration, 14 indicating a strong coupling between Ce 4f electrons and Fe 3d electrons in CeFeAsO, as previously reported by neutron scattering and muon spin relaxation measurements. 16,17 On the Co-rich side, the ferromagnetically ordered Co ions have a strong polarization effect on the AFM order of Ce moments.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the Ce(Fe,Co)AsO series, superconductivity appears while the magnetic order at T Fe N is quickly suppressed upon substituting Fe with Co. 14,15 The Ce Néel temperature slightly increases near the Fe-3d magnetic instability, but shows a nearly unchanged value on further increasing the Co concentration, 14 indicating a strong coupling between Ce 4f electrons and Fe 3d electrons in CeFeAsO, as previously reported by neutron scattering and muon spin relaxation measurements. 16,17 On the Co-rich side, the ferromagnetically ordered Co ions have a strong polarization effect on the AFM order of Ce moments.…”
Section: Introductionsupporting
confidence: 56%
“…9,10 Elemental substitutions in CeFeAsO, e.g., Fe/Co or As/P, may induce superconductivity while suppressing the magnetic order of Fe-3d electrons. [11][12][13][14][15] On the other hand, CeFePO is a paramagnetic (PM) heavy fermion metal. 1 Evidence for a magnetic quantum phase transition was shown in CeFeAs 1−x P x O, where the AFM state is separated from the PM heavy fermion state, and a ferromagnetic order develops in the intermediate doping region.…”
Section: Introductionmentioning
confidence: 99%
“…Upon substituting Fe with Co, the magnetic/structural transition is quickly suppressed and superconductivity exists over a narrow doping range. [15][16][17][18][19] In the ReO layers, partial substitution of Gd with Th suppresses the magnetic/structural transition and then gives rise to superconductivity where T sc reaches a maximum of 56 K at 20% Th. 5 Similarly, a narrow superconducting region was also observed in GdFeAsO 1−δ by introducing oxygen deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This is a very general property of the Fe-based superconductors and in fact there are only a few examples known where SC does not show up despite vanishing Fe ordering [e.g., Mn-doped LaFeAsO 7 or BaFe 2 As 2 8 ]. In this sense CeFeAs 1−x P x O presents a unique situation because of the following: First, replacing As with P "usually" results in SC as shown for AFe 2 As 2 [A = Ca, 9 Ba, 10 Sr, 9 Eu 11 ] and RFeAsO [R = La, 5 Sm 12 ], and second, CeFeAsO becomes superconducting when substituting Fe with Co 13 or O with F 14 and also by inducing oxygen vacancies. 2 But combining P doping with R = Ce among the RFeAsO compounds results in exceptional behavior: The Fe ordering is suppressed, as shown by de la Cruz et al 15 and Luo et al, 16 however, superconductivity had not yet been observed in CeFeAs 1−x P x O.…”
mentioning
confidence: 99%
“…13,14 Therefore, the origin for this behavior is more complex than a possible simple sign change of the Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction and will hopefully stimulate further theoretical investigations. For x > 70% the FM ordering of Ce becomes weaker, and for x = 90%, T C is reduced to 2.7 K. P concentrations of 90% < x 100% result in further suppression of T C , which will be the focus of a forthcoming publication.…”
mentioning
confidence: 99%